(untitled) (World Bulletin of Public Health, 2023)
This study was conducted with the aim of identifying some genetic features of the FADS1 gene and its relationship to some productive traits of local goats, studying the components of milk from protein, fat, lactose and nonprotein mineral elements, estimating the live weight of mothers, birth weight, weaning weight, length of milk season and gene-duplication, the effect of live weight was significant (P <0.05) in all genetic manifestations as well as the length of the milk season is significant (P><0.05) in most genetic manifestations and the percentage of fat in the components of milk was also significant (P><0.05), while other productive traits and milk components did not have a significant effect.>